The Sveta Lucija Hallstatt cultural group.: An introduction and brief outline - Teržan, Biba (Arheološki vestnik, 2022)
The Sveta Lucija, also known as the Posočje cultural group, inhabited the upper Posočje region and the adjacent areas of Bohinjski kot, Cerkljansko and the upper valley of the River Nadiža/Natisone in the Hallstatt period. Recent investigations have shown a denser settlement of these areas than previously thought, particularly on the foothills of the Julian Alps. The recovered small finds suggest that these foothills were inhabited in the late period of the group. In the Sv. Lucija IIa–b phases, there was an increased economic prosperity of the settlement at Most na Soči as a proto-urban centre of the whole cultural group that was very likely territorially organised. As for the associated cemetery, analyses have shed light on the influence and contacts of the Sv. Lucija group with neighbouring, but also very distant areas or cultural groups, on the one hand, and on the indications of the social structure and differentiation of the local population, on the other. An important new element with regards to the ritual-religious sphere of the Sv. Lucija cultural group are the archaeological sites in unusual natural settings, which may have been sacred places where a special kind of votive rituals were being performed. Finally, the contribution discusses literacy and ethnic identity of the population that made up the Sveta Lucija cultural group.